Intraocular femtosecond laser use in traumatic cataracts following penetrating and blunt trauma - Nagy, Zoltán Zsolt; Knorz, Michael C. (Journal of refractive surgery, 2012)
Journal of Refractive Surgery | PURPOSE:To investigate the use of femtosecond laser cataract surgery in traumatic cataracts of different origin. METHODS:The first case developed acute traumatic cataract due to penetrating injury of the cornea and the anterior lens capsule; the second developed traumatic cataract 11 years after a penetrating corneal injury; and the third developed a “white” cataract 12 months after blunt ocular